STUDENT HOUSING RIGHTS AND ADMINISTRATIVE AND LEGAL ENSURING OF STUDENT RESIDENCE - Svetlana V. Barabanova; Natalya V. Kraisman (Высшее образование в России)
The article examines students’ rights to housing in Russia and in the United Kingdom. The authors compare English and Russian systems of using a hostel, adduce conditions and rules of accommodation in hostels of York University as sample for modifying domestic housing regulatory enactments taking into account Russian mentality.